Particle identification algorithms for the PANDA barrel DIRC - Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the international accelerator Facility for Antiproton and Ion Research in Europe (FAIR) near GSI, Darmstadt, Germany will address fundamental questions of hadron physics. Excellent particle identification is required to achieve the PANDA physics goals. Hadronic particle identification (PID) in the barrel region of PANDA target spectrometer will be delivered by a fast focusing DIRC (Detection of Internally Reflecfted Cherenkov light) counter. The Barrel DIRC will cover the polar angle range of 22◦-140◦ and is designed to provide π/K separation for momenta up to 3.5 GeV/c with a separation power of at least 3 standard deviations. Several reconstruction algorithms have been developed to determine the performance of the detector. The “geometrical reconstruction” determines the Cherenkov angle by relying primarily on the position of the detected photons. The “time imaging”, however, utilizes both position and time measurements by directly performing the maximum likelihood fit. Simulations and experimental data from prototype tests at the CERN Proton Synchrotron (PS) were used to evaluate the performance of the algorithms. We will discuss both reconstruction approaches.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Detector modelling and simulations I; Interaction of hadrons with matter etc; Interaction of photons with matter; Interaction of radiation with matter; Particle identification methods; Performance of High Energy Physics Detectors